2020
DOI: 10.1590/1516-4446-2019-0547
|View full text |Cite
|
Sign up to set email alerts
|

Exercise prescription for people with mental illness: an evaluation of mental health professionals’ knowledge, beliefs, barriers, and behaviors

Abstract: The aim of this study was to understand the knowledge, beliefs, barriers, and behaviors of mental health professionals about physical activity and exercise for people with mental illness. Methods: The Portuguese version of The Exercise in Mental Illness Questionnaire was used to assess knowledge, beliefs, barriers, and behaviors about exercise prescription for people with mental illness in a sample of 73 mental health professionals (68.5% women, mean age = 37.0 years) from 10 Psychosocial Care Units (Centros d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 38 publications
1
36
1
1
Order By: Relevance
“…It is recommended that older adults perform at least 150–300 min of moderate intensity or 75–150 min of vigorous intensity physical activity or an equivalent combination of moderate intensity and aerobic physical activity of vigorous intensity, per week [ 25 ]. However, these guidelines are still underused and underestimated by health professionals in general, requiring methods to overcome these barriers [ 28 ]. The medical and sports sciences and physiotherapy, for example, have the opportunity to seek alternatives, innovations and solutions to these problems and limitations.…”
mentioning
confidence: 99%
“…It is recommended that older adults perform at least 150–300 min of moderate intensity or 75–150 min of vigorous intensity physical activity or an equivalent combination of moderate intensity and aerobic physical activity of vigorous intensity, per week [ 25 ]. However, these guidelines are still underused and underestimated by health professionals in general, requiring methods to overcome these barriers [ 28 ]. The medical and sports sciences and physiotherapy, for example, have the opportunity to seek alternatives, innovations and solutions to these problems and limitations.…”
mentioning
confidence: 99%
“… 44 A recent study suggests that new interventions must connect with existing practices, and that local management support is important when implementing health promotion initiatives in community mental health services. 20 …”
Section: Discussionmentioning
confidence: 99%
“…44 A recent study suggests that new interventions must connect with existing practices, and that local management support is important when implementing health promotion initiatives in community mental health services. 20 In the study by Mwebe, 5 mental health nurses viewed the monitoring and screening of the physical health needs of service users as vital, as they acknowledged that both physical and mental health needs were equally important and should receive the same attention from health professionals. Our study provides further nuancing to this picture.…”
Section: Discussionmentioning
confidence: 99%
“…These specialists should work with the client to tailor exercise programmes to the specific needs of their client and create cognitive and behavioural strategies to encourage personal recovery-oriented practice and develop positive behaviours towards exercise (Lederman et al 2016). Despite the benefits of exercise, mental health clinicians often do not prescribe exercise or refer to an appropriately trained physical activity specialist as part of traditionally accepted models of care for people with mental illnesses such as depression (Kleemann et al 2020;Rosenbaum et al 2018). The rationale for this is not fully understood; however, barriers may relate to mental health clinicians not being cognisant of the research supporting the benefits of exercise, lack of expertise to prescribe exercise, or not having access to or not knowing who appropriately trained physical activity specialists are (Korman et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This is notwithstanding that the evidence previously outlined demonstrating that many mental health consumers would benefit both physically and psychologically from increased exercise and physical activity (Exercise and Sports Science Australian 2017 ;Firth et al 2020;Hui et al 2021;Rosenbaum et al 2018). Despite awareness of the benefits, health professionals that do not specialize in exercise prescription have frequently identified that prescribing and or advocating for exercise is beyond their knowledge and training or acknowledged it required an exercise professional (Kleemann et al 2020;Radovic et al 2018;Way et al 2018) ), but is not common practice. Health professionals in mental health settings have identified other barriers to exercise prescription focused on the client such as concerns for their physical and mental health and difficulties with social interactions as well as adherence (Glowacki et al 2019;Radovic et al 2018;Way et al 2018).…”
Section: Introductionmentioning
confidence: 99%